Pharmacokinetics and pharmacodynamics of a proposed tocilizumab biosimilar MSB11456 versus both the US-licensed and EU-approved products: a randomized, double-blind trial. (4th May 2022) - Schwabe, Christian; Illes, Andras; Ullmann, Martin; Ghori, Vishal; Vincent, Emmanuelle; Petit-Frere, Corinne; Monnet, Joelle; Racault, Anne Sophie; Wynne, Chris
ABSTRACT: Background: Tocilizumab is a recombinant humanized monoclonal immunoglobulin G1 antibody against the interleukin-6 receptor (IL-6 R). MSB11456 is a proposed tocilizumab biosimilar. Objectives: To assess the pharmacokinetic and pharmacodynamic similarity of MSB11456 to both US-licensed and EU-approved tocilizumab. Methods: Healthy adult volunteers (N = 685) received a single 162 mg subcutaneous injection of MSB11456, US-licensed tocilizumab, or EU-approved tocilizumab in this randomized, double-blind, parallel-group study. Blood samples were taken pre-dose and for up to 48 days post-dose. Primary endpoint pharmacokinetic parameters were analyzed using analysis of covariance. Secondary pharmacodynamic measures included serum-soluble IL-6 R and serum C-reactive protein. Safety data were analyzed descriptively. Results: Pharmacokinetic equivalence (with all corresponding 90% confidence intervals for the geometric least squares mean ratios within the predefined 80.00% to 125.00% equivalence margin) was demonstrated between MSB11456 and both US-licensed and EU-approved tocilizumab, as well as between the reference products. Pharmacodynamic analyses demonstrated similarity of MSB11456 and both US-licensed and EU-approved tocilizumab, as well as between the reference products. Safety, tolerability, and immunogenicity were comparable between treatments. Conclusion: Pharmacokinetic and pharmacodynamic similarity of MSB11456, US-licensed tocilizumab, and EU-approved tocilizumab were demonstrated, and the three products had comparable immunogenicity and safety, supporting MSB11456 as a biosimilar to tocilizumab. PLAIN LANGUAGE SUMMARY: Tocilizumab is a biologic drug that is used to treat autoimmune diseases, including rheumatoid arthritis. Biologic drugs are very important for the treatment of autoimmune diseases, but their costs limit accessibility. Therefore, the availability of biosimilars, which are biologics that are very similar in structure and function to an existing biologic drug, may provide a significant cost advantage for national healthcare programs and consumers. MSB11456 is a proposed tocilizumab biosimilar. Our study tested the pharmacokinetic and pharmacodynamic similarity of MSB11456 to the approved formulations of tocilizumab in the US and EU (US-licensed and EU-approved tocilizumab) in a large group of healthy adults. Volunteers received a single 162 mg subcutaneous injection of MSB11456, US-licensed tocilizumab, or EU-approved tocilizumab in this randomized, double-blind, parallel-group study. Blood samples were taken before and regularly after the injection, and safety was monitored. We showed that the pharmacokinetics and pharmacodynamics of MSB11456, US-licensed and EU-approved tocilizumab were sufficiently similar to claim equivalence between the three products. Safety and immunogenicity were also comparable between the three treatments. These findings suggest that MSB11456 can be considered as a biosimilar to tocilizumab. Biosimilars have improved price competition and led to a reduction in the net costs of biologics, so tocilizumab biosimilars can be expected to contribute to this and potentially improve access to the best available care.